2001
DOI: 10.1029/2001gc000198
|View full text |Cite
|
Sign up to set email alerts
|

On the strength of interplate coupling and the rate of back arc convergence in the central Andes: An analysis of the interseismic velocity field

Abstract: We interpret the interseismic crustal velocity field of the central Andes using a simple three‐plate model in which the Andean mountain belt is treated as a rigid microplate located between the Nazca and South American (SoAm) plates. We assume that the Euler vectors associated with these plates are strictly coaxial and that the surface velocity field can be decomposed into an elastic loading field (driven by locking of the main plate boundary) and a smaller contribution associated with back arc convergence. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
140
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(155 citation statements)
references
References 40 publications
13
140
1
1
Order By: Relevance
“…Además la coincidencia entre la notoria desaceleración post-Mioceno de la tasa de convergencia (Somoza, 1998) y el hecho que las magnitudes de los desplazamientos observados evidencian que los procesos de deformación han sido menos efectivos después del Mioceno, indica una relación causal entre la mecánica del oroclino, la velocidad de convergencia y la naturaleza de la deformación estudiada. Allmendinger et al (2005a) explican el acortamiento paralelo al margen, evidenciado por las fallas en estudio, como el resultado de la subducción de una placa bajo un margen curvo preexistente, idea que es apoyada en modelos elásticos publicados por Bevis et al (2001). Sin embargo, este modelo no explica el acortamiento subordinado ortogonal al margen evidenciado en este trabajo.…”
Section: Síntesis Y Discusiónunclassified
“…Además la coincidencia entre la notoria desaceleración post-Mioceno de la tasa de convergencia (Somoza, 1998) y el hecho que las magnitudes de los desplazamientos observados evidencian que los procesos de deformación han sido menos efectivos después del Mioceno, indica una relación causal entre la mecánica del oroclino, la velocidad de convergencia y la naturaleza de la deformación estudiada. Allmendinger et al (2005a) explican el acortamiento paralelo al margen, evidenciado por las fallas en estudio, como el resultado de la subducción de una placa bajo un margen curvo preexistente, idea que es apoyada en modelos elásticos publicados por Bevis et al (2001). Sin embargo, este modelo no explica el acortamiento subordinado ortogonal al margen evidenciado en este trabajo.…”
Section: Síntesis Y Discusiónunclassified
“…A dense network of continuous GPS (cGPS) stations was installed in the Maule region after the main shock (Bevis et al 2010;Vigny et al 2011) densifying the existing cGPS network (Bevis et al 2001;Ruegg et al 2009;Vigny et al 2009). The large number of GPS stations allows an unprecedented spatio-temporal resolution of the rapidly time-varying postseismic response in near, medium and far-fields following a large subduction earthquake.…”
Section: Gps Observations and Afterslip Modelmentioning
confidence: 99%
“…Reilinger et al [2006] divided the region into blocks, and they showed 4.4 AE 0.5 (1s) mm/yr of shortening across this region, with a much larger component of left-lateral shear ($15 mm/yr) across it. [54] Andes (Northern Bolivia and Southern Peru) (NBA and SPA): We rely on the GPS results of Bevis et al [2001] and Kendrick et al [2001], and the analysis by Allmendinger et al [2007], which shows convergence rate of 6 AE 2 mm/yr. These results supersede those of Norabuena et al [1998], who reported a somewhat higher rate.…”
Section: Appendix B: Summary Of Geodetic and Other Constraints On Shomentioning
confidence: 99%
“…[56] Andes (Southern Bolivia) (SBA): We use the GPS results of Bevis et al [2001], showing a convergence rate of Figure A3. Histograms of "raw" factors of the normalized multivariate linear regressions of topographic variables against V h , precip, and coslat, with 1s error bars, from Tables 3b and 3c (active and inactive ranges taken separately).…”
Section: Appendix B: Summary Of Geodetic and Other Constraints On Shomentioning
confidence: 99%
See 1 more Smart Citation